Socioeconomic Changes In The Community After Switching To Mining In Jorong Tanjuang Bungo, Nagari Ganggo Hilia, Bonjol District, Pasaman Regency - Endah Khairani; Faishal Yasin; Sri Rahmadani (UNIB Press, 2025)
This study examines the socioeconomic transformation of the community in Jorong Tanjuang Bungo, Nagari Ganggo Hilia, Bonjol District, Pasaman Regency, which shifted its main livelihood from agriculture to small-scale gold mining. The transition was driven by volatile agricultural incomes and the economic appeal of gold mining, which promised higher and faster returns. The research aims to describe and analyze changes in the community's social and economic conditions before and after the shift to mining. Using a qualitative descriptive approach grounded in Marvin Harris's Cultural Materialism theory, data were collected through in-depth interviews, observations, and documentation with ten purposively selected informants, including local leaders and miners. The findings reveal that, before mining, the community lived modestly, with low incomes, limited education, and strong collective farming practices. After entering the mining sector, household income increased significantly, and families began investing in housing and education. However, social relations weakened, work systems became hierarchical, and lifestyles shifted toward material consumption. The study concludes that the transition to gold mining improved economic welfare but also reshaped social structures and cultural values. Consistent with Harris's framework, the change in economic infrastructure led to transformations in social structure and cultural superstructure, reflecting a shift from agrarian subsistence values to extractive and consumption-oriented ones.